PROFILE ANALISYS OF THE PHYSICAL AND ANTHROPOMETRICAL ABILITIES IN ATHLETES UNDER-18 FROM THE SOCCER CLUB UNIÃO CACOALENSE/RO. (Fiep Bulletin - online, 2011)
INTRODUCTION: Football is a complex activity, requiring the player's development of various physical, motor and psíquicas.OBJETIVO: analyzing the profile of a physical football team under 18 years of the city of Cacoal - RO.MATERIAIS AND METHODS : the research involved a sample of 23 athletes, which is a choice for convenience. This research is classified as cross-correlation with qualitative-quantitative approach. For data collection tests were used for 12 minutes of COOPER to analyze the aerobic capacity by VO2 max. To check the speed test was used for 50 meters and the body composition was used FORSYTH & Sinningia where it is used for 2 sub-scapular skinfolds and abdominal.RESULTADOS: the variables for analysis of body composition showed the sample mean and standard deviations of weight, height and body fat percentage follows: 71.15 and 7.15, 173.79 and 1.04, 11.3 and 1.2 and mean age 16.5 and sd 2.3. For the variables of physical means and standard deviations of the test 12 minutes, speed and VO2 were 2373.38 and 397.52, 6.77 and 0.44, 41.54 and 12.4. CONCLUSION: it can be conclude that the sample is evaluated with good fitness.
Keywords: physical; anthropometric and football